A Multimodal Virtual Reality Inventory System - Ko, Kenneth King L. (Archīum Ateneo, 2023)
Applications involving virtual reality (VR), especially VR-based video games, integrate multiple gameplay mechanics. One such mechanic is an inventory system, which is a way for a player to manage their items in an easy and convenient manner. This study aims to iterate upon previous studies and implementations of inventory management to produce a new inventory system framework for use in VR adventure and serious games, with a primary focus on improving ease of use, convenience, and accessibility for a more refined and more immersive experience. The framework allows for different modalities, including control via vision-based hand tracking and traditional controllers. The study finds that the inventory systems implemented using the framework were able to satisfy essential user requirements criteria and improve upon existing implementations found in related literature, indicating that the framework is functional. Additionally, the study also finds that vision-based hand tracking provides a similar user experience as traditional controllers in terms of immersion, despite some tracking inaccuracies experienced when utilizing the former modality.